2016
DOI: 10.33549/physiolres.933524
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemic Rats Fed High Fat Diet as a Model of Metabolic Syndrome

Abstract: People with metabolic syndrome have higher risk of cardiovascular diseases then those without. The aim of the work was to investigate whether high fat diet administered to Prague hereditary hypertriglyceridemic (HTG) rats can induce signs of metabolic syndrome (MetS). Our results showed that HTG rats fed high fat diet (HTGch) had disturbed glucose metabolism and also lipid metabolism – increased serum triacylglycerols (TAG), total cholesterol (Ch), low-density lipoprotein-Ch (LDL-Ch), and decreased high-densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
2
10
1
Order By: Relevance
“…In conclusion, even though obesity was not present in HTG-FRD rats, marked morphological alterations in the liver, such as hepatomegaly with the presence of steatosis, were observed as a result of FRD. Based on this observation as well as on results presented in our previous work (Kaprinay et al 2016), HTG rats on FRD could serve as an experimental tool for the study of metabolically unhealthy non-obese individuals. The fat-rich diet-induced thickening of the abdominal aorta wall suggests most likely impaired vascular elasticity.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In conclusion, even though obesity was not present in HTG-FRD rats, marked morphological alterations in the liver, such as hepatomegaly with the presence of steatosis, were observed as a result of FRD. Based on this observation as well as on results presented in our previous work (Kaprinay et al 2016), HTG rats on FRD could serve as an experimental tool for the study of metabolically unhealthy non-obese individuals. The fat-rich diet-induced thickening of the abdominal aorta wall suggests most likely impaired vascular elasticity.…”
Section: Discussionsupporting
confidence: 59%
“…To mimic MetS-like conditions, the model of hypertriacylglycerolemic (HTG) rats was established (Zicha et al 2006). Moreover, we found and published recently (Kaprinay et al 2016) that hypertriacylglycerolemia of these rats combined with fat-rich diet (FRD) resulted in markedly disturbed lipid metabolism expressed by increased total cholesterol and low-density lipoprotein-cholesterol, decreased high-density lipoprotein-cholesterol and disturbed glucose metabolism, compared to HTG rats fed standard diet (SD). These changes in the serum lipidic profile were accompanied with oxidative stress and tissue damage identified as increased liver concentrations of thiobarbituric acid reactive substances and increased specific activity of the lysosomal enzyme N-acetyl-β-D-glucosaminidase.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Vascular endothelial dysfunction, which can lead to atherosclerosis, belongs to the first signs of cardiovascular disorders (Oostrom et al, 2002). In our previous work (Kaprinay et al 2016), we found that hypertriglyceridemic rats fed high fat, high cholesterol diet (HTGChol) are suitable non-obese models of MS, however, without significant changes in the vascular endothelium. The most important components of MS are hyperglycemia and glucose intolerance that are accompanied with oxidative stress − reduction of antioxidant activity and increased production of reactive oxygen species ( The aim of the work was to find an experimental model suitable for the study of endothelial dysfunction induced by MS. We used hypertriglyceridemic rats (HTG) that were fed a hypercholesterolemic diet of different composition and duration: a 6-week administration of standard diet with an addition of cholesterol and fat (HTGChol) and a three-month administration of the same diet with an addition of fructose (HTGCholF).…”
mentioning
confidence: 99%
“…HFFD was enriched with 10% of fructose, 7.5% of lard and 1% of cholesterol. The experimental model of metabolic syndrome was designed and prepared at the Institute of Experimental Pharmacology and Toxicology, Centre of Experimental Medicine of the Slovak Academy of Sciences (Kaprinay et al, 2016;.…”
Section: Methodsmentioning
confidence: 99%